The contribution of low birth weight to severe vision loss in a geographically defined population. Issue 1 (1st January 1998) - Crofts, Barbara J; King, Rosemary; Johnson, Ann
Abstract : AIMS: To describe the birthweight specific rate of severe vision loss among babies born between 1 January 1984 and 31 December 1987 to mothers resident in a geographically defined area, to classify the causes of vision loss by time of origin, and to describe the associated sensory and motor impairments and disabilities. METHODS: Cases were identified from a population register of children with early childhood impairment, which uses multiple sources of ascertainment. Further clinical information was retrieved from hospital records and by asking ophthalmologists caring for the children. RESULTS: 166 (1.25/1000 live births) children with severe vision loss diagnosed by the age of 5 years were identified. The rate among babies born weighing less than 1500 g at birth was 26 times higher than the rate for babies between 2500 g and 3499 g. These very low birthweight babies contribute 17.5% of all severely visually impaired children. Almost two thirds of children with severe vision loss have a lesion of prenatal origin. Other sensory or motor deficits are present in 69% of the children. Retinopathy of prematurity accounted for 5.4% of all visually impaired children and seven of the 166 children met the criteria for perinatal asphyxia. CONCLUSIONS: Although the contribution made by babies with a low birth weight to overall severe vision loss in the community is small, many of these children have additional impairments and probably place considerable demands on health and educational services and families. Reduction in the frequency of vision problems in the preschool population as a whole is unlikely to occur until there are major advances in the understanding of the aetiology and prevention of eye conditions of genetic, prenatal, and developmental origin.